Mycoflora associated with Pigeon pea and Chickpea - Patil, D P; Pawar, P V; Muley, S M (International Multidisciplinary Research Journal, 2012)
Pigeonpea (Cajanu. cajan.) and Chick Pea (Cicer arietinum) are major pulse crops grown in India. The seed mycoflora was screened by using agar plate method. seeds of varieties of these pulse crops was used in the study and results were obtained from untreated and treated seeds. The untreated seeds were found to be associated with highest percent incidence of mycoflora. In case of untreated seeds the percent incidence of Aspergillus flavus (30%) was the highest followed by A. niger (25%), Penicillium notatum (20 %), Cladosporium herbarum (18%), where as all other fungi were within the range of (3 to 15%).